Traditional knowledge of medicinal flora among tribal communities of Buner Pakistan - Saddiq Ur Rahman; Zahid Ullah; Ahmad Ali; Muhammad Abdul Aziz; Naveed Alam; Hassan Sher; Iftikhar Ali (Elsevier, 2022)
Background: This study provides a comprehensive documentation of traditional knowledge about plant based recipes used for the treatment of human ailments by tribal communities of Buner Pakistan. The aim of the study was to understand the dynamics and threats to traditional knowledge (TK) and to investigate the potential implications of this knowledge in future economic development in the region in light of China-Pak economic corridor. Methods: The studies were conducted from 2016 to 2020 in 36 major villages of district Buner Pakistan, via 137 key informants, using semi-structured interviews, open ended questionnaires, group discussions, and transit walks. The data were analyzed using different quantitative indices including Informant Consensus Factor (ICF), Use value (UV), Relative frequency citation (RFC), Relative importance index (RI) and Cultural importance index (CI). Results: This study revealed 282 plant species belonging to 94 families, including one fungal taxon, two ferns and 5 gymnosperms used as ethnomedicine. Herbs were the dominant growth form (57.80% spp), leaves formed the most used part (41% spp) and most of the rcipes were prepared in boiling water (55.67%). The most important medicinal plant families on the basis of use reports (UR) were Fabaceae (306 UR), Lamiaceae (256 UR), Rosaceae (210 UR), Amaranthaceae (180 UR) and Asteraceae (159 UR). Twelve different disease categories were identified, among which gastrointestinal diseases (1020 UR), and cardio-vascular diseases (972 UR) formed the largest categories. The important species on the basis of use reports included Berberis lyceum, Azadirachta indica, Prunus dulcis, Skimmia laureola, and Mentha longifolia with 80, 64, 62, 58, and 55 use reports respectively. These species also scored highest cultural importance values (CI) of 0.58, 0.47, 0.45, 0.42, and 0.40 respectively. On the basis of relative frequency of citation (RFC) values, the top five species were Medicago polymorpha 0.51, Skimmia laureola 0.35, Berberis lycium 0.33, Justicia adhatoda 0.30, and Ziziphus oxyphylla 0.29. Some interesting novel uses of plants included, the use of Heracleum candicans leaves against highblood, Arisaema jacquemontii as aphorodesiac, and Dysphania ambrosioides for stomach pain. Conclusion: This study reported many new uses, and novel medicinal plant species (Bombax ceiba, Mimosa himalayana, Lycopus eropaeus, Salix acmophylla, Corydalis cornuta, Galium aparine) for the first time from the region. The study concluded that mountainous rural people of Buner possess a rich heritage of ethnobotanical knowledge, which was not previously documented comprehensively. This study provides a base for further pharmacological and phytochemical evaluation of medicinal flora.